2020
DOI: 10.1371/journal.pone.0235889
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations between internet use and poor mental health: A population-based study

Abstract: Objectives Most of the evidence on the effects of internet use on mental health derives from cross-sectional research. We set out to explore prospective associations between internet use (hours online and specific internet experiences) and future mental health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
2
20
1
Order By: Relevance
“…The study by Kokka et al revealed that problematic internet use has a negative impact on the sleep and health of teenagers in Athens [ 27 ]. Using 1431 respondents in the UK, Mars’ study found that excessive internet use increased the risk of depression in UK women (highest tertile vs lowest tertile OR = 1.41, 95% CI 0.90 to 2.20) [ 28 ]. Xie found that Internet use affected the mental health of older adults and increased their incidence of depressive symptoms [ 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study by Kokka et al revealed that problematic internet use has a negative impact on the sleep and health of teenagers in Athens [ 27 ]. Using 1431 respondents in the UK, Mars’ study found that excessive internet use increased the risk of depression in UK women (highest tertile vs lowest tertile OR = 1.41, 95% CI 0.90 to 2.20) [ 28 ]. Xie found that Internet use affected the mental health of older adults and increased their incidence of depressive symptoms [ 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Carter et al, 2020 found no relationship between sedentary behavior and mood [ 13 ]. Four other studies showed no correlation between sedentary behavior and anxiety, stress, and depression [ 11 , 44 , 45 , 46 ]. Of the 10 studies, four (40% including two high-quality studies [ 34 , 40 ]) indicated that sedentary behavior resulted in emotional disorders.…”
Section: Resultsmentioning
confidence: 99%
“… Self-harm and suicide : the White Paper cites academic research that showed that 22.5% of young adults reported suicide and self-harm-related internet use; 70% of young adults with suicidal intent reported related internet use; approximately a quarter of children who presented to hospitals following self-harm, and of those who died of suicide, reported suicide-related internet use. 8 Underage sharing of sexual imagery : the White Paper cites statistical evidence that suggests that between 26% and 38% of teenagers have sent sexual images to partners, whereas 12% to 49% of teenagers have received sexual images from partners. Online disinformation : the White Paper cites a Reuters report showing that 61% of people want the government to do more to distinguish between real and fake news.…”
Section: An Overview Of the Online Safety Billmentioning
confidence: 99%
“…Self-harm and suicide : the White Paper cites academic research that showed that 22.5% of young adults reported suicide and self-harm-related internet use; 70% of young adults with suicidal intent reported related internet use; approximately a quarter of children who presented to hospitals following self-harm, and of those who died of suicide, reported suicide-related internet use. 8 …”
Section: An Overview Of the Online Safety Billmentioning
confidence: 99%